Neurovascular Study of the Trigeminal Nerve at 3T MRI. Issue 1 (February 2015) - Docampo, Jorge; Gonzalez, Nadia; Muñoz, Alexandra; Bravo, Fernando; Sarroca, Daniel; Morales, Carlos
This study aimed to show a novel visualization method to investigate neurovascular compression of the trigeminal nerve (TN) using a volume-rendering fusion imaging technique of 3D fast imaging employing steady-state acquisition (3D FIESTA) and coregistered 3D time of flight MR angiography (3D TOF MRA) sequences, which we called "neurovascular study of the trigeminal nerve". We prospectively studied 30 patients with unilateral trigeminal neuralgia (TN) and 50 subjects without symptoms of TN (control group), on a 3 Tesla scanner. All patients were assessed using 3D FIESTA and 3D TOF MRA sequences centered on the pons, as well as a standard brain protocol including axial T1, T2, FLAIR and GRE sequences to exclude other pathologies that could cause TN. Post-contrast T1-weighted sequences were also performed. All cases showing arterial imprinting on the trigeminal nerve (n = 11) were identified on the ipsilateral side of the pain. No significant relationship was found between the presence of an artery in contact with the trigeminal nerve and TN. Eight cases were found showing arterial contact on the ipsilateral side of the pain and five cases of arterial contact on the contralateral side. The fusion imaging technique of 3D FIESTA and 3D TOF MRA sequences, combining the high anatomical detail provided by the 3D FIESTA sequence with the 3D TOF MRA sequence and its capacity to depict arterial structures, results in a tool that enables quick and efficient visualization and assessment of the relationship between the trigeminal nerve and the neighboring vascular structures.